Drawing the mind: assessing cognitive decline through self-figure drawings - Goldner, Limor; Pery, Amit; Czamanski-Cohen, Johanna; Jaroenkajornkij, Alex Nisara; Ben-Bassat, Aviel; Avraham, Gefen; Binson, Bussakorn; Lev-Wiesel, Rachel (Frontiers in Psychology, 2025)
BackgroundDrawing requires the integration of visual perception, spatial processing, motor planning, and executive functions, but few studies have explored the potential connection between drawings, cognitive decline and dementia.AimThis study compared self-figure drawings of elderly individuals with Alzheimer’s disease (AD) and mild cognitive impairment (MCI) to those with normative cognitive functioning.MethodA total of 496 older adults from Thailand and Israel (Mage = 73.97, 70% women) participated in this study. Participants completed the Montreal Cognitive Assessment (MoCA-5) and then engaged in a self-figure drawing task. The drawings were categorized into eight groups based on their graphic characteristics. MANCOVA was used to examine differences between the drawing groups, t-tests were used to examine cultural differences, and Chi-square tests were used to examine differences and associations between the drawing groups and the MoCA-5 scores or categories.ResultsWe found that normative cognitive performance was associated with adapted portraits, whereas moderate to severe impairment correlated with schematic, disorganized, and unusual portraits. Cultural differences were also observed: the Thai participants had higher MoCA-5 scores than their Israeli counterparts and fewer differences in drawing group distribution.ConclusionThese findings suggest that self-figure drawings may reflect the cognitive status of older adults, with more detailed and adapted drawings indicating better cognitive functioning.Implications for practiceSelf-figure drawings can be used as a complementary tool for assessing cognitive decline in diverse populations. However, cultural differences in drawing styles and cognitive test performance underscore the need for culturally sensitive approaches to dementia assessment and research.